KEPEMIMPINAN DAN LOYALITAS TERHADAP KINERJA KARYAWAN RSJ MENUR SURABAYA - Adiwibowo, A. Suyunus (Department of Management, 2012)
KEPEMIMPINAN DAN LOYALITAS TERHADAP KINERJAKARYAWAN RSJ MENUR SURABAYAA. Suyunus AdiwibowoRumah Sakit Asrama Haji SurabayaE-mail: as_adiwibowo@yahoo.co.idABSTRACTThis study?s purpose were: 1) To know and analyze whether the commitment, loyalty and discipline ofwork simultaneously influence to the ability of employees at Menur regional mental hospital, Surabaya.2) To know and analyze if commitment, loyalty and discipline of work can partially affect the ability ofemployees, 3) To know and analyze which among commitment, loyalty and discipline of work have themost dominant influence on the ability of employees at Menur regional mental hospital. Data wascollected from employees at the regional mental hospital by using questionnaires. Analyses method usesmultiple linear regression analysis, correlation coefficient, coefficient of determination, simultaneoustests and partial tests. The result of this study indicate that commitment, loyalty and discipline of workhave significant influences on the ability of the regional mental hospital employees simultaneously andpartially, while the most dominant influence is work discipline.Keywords: commitment, loyalty, discipline and ability to work of employees.